Home automation exerting internet of things with child electric exposure precaution system - Barua, Sayannha; Shamab, Oshama Omayes; Afri, Tammim; Abdullah, Jawad (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.